SISTEM SUBTITUSI AIR PADA AKUARIUM BERBASIS INTERNET OF THINGS (IOT) - Sahrul Ramdani Nugraha; Agus Ramdhani Nugraha (LPPM Unbaja, 2025)
The progress and development of technology today is very rapid, many people are utilizing technological advances as a means to conduct various kinds of business. Every activity carried out by the community is very dependent on information and communication technology tools that exist today, therefore a system is needed that can monitor changes in water conditions, in the room. Identify previous studies relevant to the topic, both successful and those that still have shortcomings. Analyzing user needs, both from the perspective of aquarium owners to researchers in the context of technical needs. Water turbidity is an important parameter that can affect the health of aquatic organisms in an aquarium. Basic concepts of the Internet of Things (IoT), including network architecture, communication protocols, and commonly used IoT platforms such as Blynk, Thingspeak, or other cloud-based platforms. By utilizing IoT, the water substitution system in aquariums becomes more efficient and automated, incorporating sensors, controllers, and internet connectivity to monitor and manage water conditions. The system aims to maintain the water quality in the aquarium by replacing the old water regularly as needed as determined by the sensors, thus providing a healthy environment for fish and other aquatic organisms.